The Effectiveness of a Massive Open Online Course (MOOC) Environment in a Higher Education Institution in Malaysia - Yue, Wong Seng; Attaran, Mohammad (Journal of Informatics and Mathematical Sciences, 2017)
Massive Open Online Course (MOOC) has disrupted the worldwide educational system and brought to effective changes in the existing higher education system. Openness, diversity, availability and affordability of MOOC offer participants the high quality learning contents and encourage lifelong learning with technology enhancement. However, MOOC still troubled with pedagogical issues, assessment, students-instructor respond system, limited interaction and low completion rate. Thus, this study aimed to evaluate the effectiveness of MOOCs that has been launched in a higher education institution in Malaysia. This study will discuss the effectiveness of MOOC, based on seven evaluation factors: (1) flexibility; (2) content; (3) pedagogical; (4) lifelong learning; (5) network learning; (6) openness and (7) self-organized learning. Participants are 40 students from a local higher education institution. The analysis of collected data uncovered the extend participants’ perception in impacts and efficiency of MOOC for their future learning environment. Overall findings have shown that high satisfaction towards MOOC learning environment, with average mean score of 4.00 and above, especially for openness, flexibility, pedagogical and self-organized learning level of MOOC. Of seven evaluation factors, openness factor has achieved a highest average mean score of 4.59, highest satisfaction level from the students’ perspective on MOOC.